Analisis Terhadap Risiko Hukum Pemberian Kredit Perbankan dengan Jaminan Personal Guarantee tanpa Penyertaan Agunan Fixed Asset - Rachmat Arnanda; Dhea Tisane Ardhan; Ratna Khoirunnisa (Account : Jurnal Akuntansi, Keuangan dan Perbankan, 2023)
Banking institution becomes the main pillar in the implementation of state development activities, therefore the provision of bank credit must pay attention to the risks that will arise, but not only limited to legal risks. Provision of bank credit must be accompanied by the provision of guarantees to carry out security from a legal perspective .In addition to asking for guarantees from customers, bank must also look at the collateral priority scale that will be the guarantee. By making fixed asset collateral as the main scale in granting credit, it is a good first step to mitigate risks, because if the customer defaults on the promise (wanprestasi), the bank gets a reimbursement from the sale (auction) of the collateral goods. However, if the bank makes individual collateral as the main collateral without the inclusion of fixed asset collateral, then the level of risk of granting credit is very high at the time the customer defaults on the promise, so the execution process cannot be instantaneous through the sale (auction) considering that individual collateral does not have a special position. The execution of individual collateral can only be done if there is a court decision with permanent legal force. This research will be presented by the author in normative form. Keywords: Law Risk, Financing, Personal Guarantee, Fixed Asset